Development of Low Cost Radio-Controlled Cars Dynamometer - Mohd Zain, Mohammad Aidil Ashraf; Zulkifli, Abd Fathul Hakim (Journal of Automotive Powertrain and Transportation Technology, 2023)
A dynamometer, often known as a dyno, is a tool used to concurrently measure the rotational speed (rpm) and torque of a moving motor or engine to determine the power output at any given moment. A dynamometer is utilized as part of a testbed for numerous engine development tasks in addition to measuring the power produced by the engine or motor. This study aims to develop a low cost Radio-controlled (RC) cars dynamometer using the concept of small scale chassis dynamometer with size range from 1/20 (12cm-7cm) to 1/10 (35cm-43cm) which can establish the value of RPM, torque and horsepower. In this study, a dynamometer is developed using aluminum profile with size 20mm x 20mm for the chassis with a N35 magnet with size 10mm x 20mm that attached to the gravity roller 50mm x 200mm. The LM393 Hall effect magnetic sensor that connected to Arduino Uno R3 will detect the rotation of the magnet at the roller to calculate RC car RPM, Torque and Horsepower that will be displayed on the Arduino L2C Serial LCD. The result is verified using tachometer to compare the value of the RPM, Torque and Horsepower which provide the percentage error of 0.107%. This dynamometer has potential for STEM activity in the Design and Technology (RBT) subject for student learning in school.